Guardianship in Action (GIA) Within Brisbane Suburbs: Examining the Relationship Between Guardianship Intensity and Crime, and Changes Across Time. (September 2017) - Moir, Emily; Stewart, Anna; Reynald, Danielle M.; Hart, Timothy C.
Using Reynald's guardianship in action (GIA) model, direct observations of properties along high- and low-crime street segments, within one low-crime and one high-crime suburb of Brisbane, Australia, were conducted ( N = 1, 113). Multiple observations of properties were recorded across multiple times of the day and day of the week, in order to determine (a) the guardianship intensity exhibited by suburban residents, (b) whether areas that experience different levels of property crime were associated with different levels of guardianship intensity, and (c) whether guardianship intensity differed across time of day and day of week. Results show that guardianship intensity was significantly higher on the high-crime street segments. Although levels of occupancy differed significantly in line with expected routine activity patterns, there were no significant differences in monitoring and intervention behaviors observed over time. Current findings are discussed in light of the unique suburban residential context of Brisbane, and avenues for future research are examined.